Management of anthracnose and blight diseases of Houttuynia cordata Thunb. with fungicides - Shamsi, Shamim; Saha, Trisha (Journal of Bangladesh Academy of Sciences, 2015)
Two types of symptoms, namely anthracnose and blight were recorded on Houttuynia cordata Thunb. during the period of April to December 2013. The isolated fungi from the diseased plants were Alterneria alternata (Fr.) Keissler and Colletotrichum gloeosporioides (Penz.) Sacc. Five fungicides viz., Bavistin DF, Dithane M-45, Indofil, Salcox 50 WP and Tall 25 EC were evaluated against the pathogenic fungi at 100, 200, 300, 400 and 500 ppm concentrations. Tall 25 EC was found most efficient inhibitor of the test fungi followed by Bavistin, Indofil, Dithane M-45 and Salcox. In vivo treatment Tall 25 EC was found most effective in controlling the diseases. Journal of Bangladesh Academy of Sciences, Vol. 39, No. 1, 83-90, 2015